Immersive role-playing with avatars leads to adoption of others’ personalities - Sakuma, Hiroshi; Takahashi, Hideyuki; Ogawa, Kohei; Ishiguro, Hiroshi (Frontiers in Virtual Reality, 2023)
In modern society, where nations and even individuals are divided, building bridges between people of different personalities and backgrounds is essential to achieve harmonious coexistence. In recent years, research has been conducted on the use of technologies to bridge this gap. In this study, the effectiveness of using immersive virtual reality (IVR) technology to play the role of a stranger in helping people learn about and empathize with others was investigated. Specifically, participants were asked to role-play a first-time stranger in an IVR environment after being given prior information about the stranger via a preparatory video. The effects of role-playing between acting as a target stranger through his or her avatar in an immersive environment, acting through a different avatar in an immersive environment, and acting through his or her avatars in a non-immersive interface were compared. The results showed that using IVR technology with an exact avatar to play the target person was found to have the greatest effect on the participants' personalities and thoughts as well as increasing their empathy for that individual. This finding suggests that IVR technology may be an effective tool for bridging the gap between people from different backgrounds.